2018
DOI: 10.1002/celc.201801050
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Sacrificial Template Synthesis of a Nitrogen‐Doped Microstructured Carbon Tube as Electrocatalyst for Oxygen Reduction

Abstract: The development of low‐cost, efficient and stable electrocatalysts for the oxygen reduction reaction (ORR) is desirable but remains a great challenge. We report a self‐sacrificial template synthesis approach for nitrogen‐doped hollow carbon microtubes as electrocatalyst for ORR. Typically, Fe‐MIL (Materiaux de l'Institute Lavosier) nanocrystals cast as self‐sacrificial template. Polyaniline (PANI) was in situ‐synthesized and deposited on the surface of Fe‐MIL nanocrystals. By a two‐step pyrolysis of the MIL‐10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“… 86 E onset = 0.93 V C-PANI-MIL-2 E 1/2 = 0.87 V 0.1 M KOH Yang et al. 87 E onset = 1.0 V C-FeHZ8@g-C 3 N 4 -950 E 1/2 = 0.845 V 0.1 M KOH 80,000 s retain 91.6% Deng et al. 88 E onset = 0.97 V H-Fe-N x -C E 1/2 = 0.92 V 0.1 M KOH Yang et al.…”
Section: Applications Of Mof Nanocrystal-derived Hollow Porous Materialsmentioning
confidence: 99%
“… 86 E onset = 0.93 V C-PANI-MIL-2 E 1/2 = 0.87 V 0.1 M KOH Yang et al. 87 E onset = 1.0 V C-FeHZ8@g-C 3 N 4 -950 E 1/2 = 0.845 V 0.1 M KOH 80,000 s retain 91.6% Deng et al. 88 E onset = 0.97 V H-Fe-N x -C E 1/2 = 0.92 V 0.1 M KOH Yang et al.…”
Section: Applications Of Mof Nanocrystal-derived Hollow Porous Materialsmentioning
confidence: 99%
“…To design catalysts on hollow carbon tubes for fuel cells with nonprecious metal-based microstructures, Yang et al [273] synthesized hollow carbon microtubes doped with nitrogen as carriers to prepare Fe single-atom catalysts by a self-sacrificial template synthesis approach called C-PANI-MIL (Materiaux de l'Institute Lavosier)-SP (second pyrolysis). Figure 11a illustrates the fabrication procedure, in which Fe-MOF nanocrystals are used as the selfsacrifice template.…”
Section: Synthetic Templatesmentioning
confidence: 99%
“…Yi et al reported a self-sacrificial template synthesis of nitrogen-doped hollow carbon microtubes as an ORR electrocatalyst [ 127 ]. Polyaniline was deposited on Fe-MIL (Materials of Institut Lavoisier (MOF class)) nanocrystals, and subsequent two-step pyrolysis yielded microstructured carbon tubes with Fe 3 O 4 nanoparticles encapsulated inside their walls.…”
Section: Mof-based Orr Electrocatalystsmentioning
confidence: 99%